2000
DOI: 10.1177/004947550003000113
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics and Risk Factors of First Febrile Seizures: A Jordanian Experience

Abstract: A prospective study of 203 children admitted with a first febrile seizure was carried out over 18 months. Aseptic meningitis was diagnosed in nine children (4%). The mean age of the children was 19.9 months and the peak age incidence (88%) was between 6 months and 3 years. Complex seizures were seen in 16 cases (8%). There was a history of perinatal asphyxia in 16 patients (8%), positive family history of epilepsy in 3%, of first degree relatives and a history of febrile seizures in siblings in 13%. Upper resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 22 publications
2
28
1
5
Order By: Relevance
“…This is similar to 37% reported by Al-Eissa et al [21]. A lower incidence of positive family history ranging from 10.2-25% has been reported in other studies [22,24,28,29]. Furthermore, positive family history of epilepsy in 17% of patients in the present study was higher than 3 −14.6% reported from other places [24,29].…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to 37% reported by Al-Eissa et al [21]. A lower incidence of positive family history ranging from 10.2-25% has been reported in other studies [22,24,28,29]. Furthermore, positive family history of epilepsy in 17% of patients in the present study was higher than 3 −14.6% reported from other places [24,29].…”
Section: Discussionsupporting
confidence: 89%
“…In a study by Gohnston, the author highlighted the genetic role for the occurrence of disease and that the illness is an autosomal disease [2]. In other studies it was revealed that the prematurity and labor difficulties [3] and prenatal asphyxia [9] to be considered as important risk factors of febrile seizures. In the past, there were some considerations for viruses playing a role in appearance of febrile seizures, nevertheless, a study by Chung showed that there was no discrepancy in role of Influenza viruses, Parainfluenza viruses, and Adenoviruses and that the risk of febrile seizures is lower following the rotaviral infections [10].…”
Section: Discussionmentioning
confidence: 99%
“…1 Upper airway viral infections are the most common triggering factors. 3,4 The risk of subsequently developing epilepsy is 6.9% 5 ; although they have an excellent prognosis, they bring anxiety to parents and family members. 6 The clinical signs of febrile seizures are not different among populations, but the clinical and demographic characteristics are not identical in the different parts of the world, 7 thus justifying the necessity of the present study.…”
Section: Introductionmentioning
confidence: 99%